2022
DOI: 10.4315/jfp-21-400
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella enterica 4,[5],12:i:−, an Emerging Threat for the Swine Feed and Pork Production Industry

Abstract: Salmonella continues to be a significant cause of foodborne illnesses in human medicine. The Centers for Disease Control and Prevention reported Salmonella as the second leading cause of foodborne illness in the United States, and the leading cause of both hospitalizations and deaths. Salmonella enterica 4,[5],12:i:- (STM) is a monophasic variant of S. Typhimurium and it is an emerging threat to both human and animal health. STM was first identified in the 1980’s from poultry products and has become increasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Therefore, while uncertainties on the available analytical methods prevent a robust exposure assessment, data indicate that the use of FA as preservative in feedingstuffs may lead to a limited increase of residues in edible tissues and products with little impact, if any, on the overall consumer exposure. Hence, FA under the proposed conditions of use does not lead to an appreciable risk for consumers ( 64 66 ).…”
Section: Case Study 3: Use Of Formaldehyde As Preservative In Feedstu...mentioning
confidence: 92%
See 4 more Smart Citations
“…Therefore, while uncertainties on the available analytical methods prevent a robust exposure assessment, data indicate that the use of FA as preservative in feedingstuffs may lead to a limited increase of residues in edible tissues and products with little impact, if any, on the overall consumer exposure. Hence, FA under the proposed conditions of use does not lead to an appreciable risk for consumers ( 64 66 ).…”
Section: Case Study 3: Use Of Formaldehyde As Preservative In Feedstu...mentioning
confidence: 92%
“…The available residue studies confirmed that the use of FA in feeds increased the concentrations in meat and milk, however the concentrations found in the residue studies were still in the range of the reported background concentrations in foods. Literature data indicate a contribution <20% by FA residues (from whatever source) in foods of animal origin to the overall dietary intake of FA ( 64 , 65 ). Therefore, while uncertainties on the available analytical methods prevent a robust exposure assessment, data indicate that the use of FA as preservative in feedingstuffs may lead to a limited increase of residues in edible tissues and products with little impact, if any, on the overall consumer exposure.…”
Section: Case Study 3: Use Of Formaldehyde As Preservative In Feedstu...mentioning
confidence: 99%
See 3 more Smart Citations